2001
DOI: 10.1007/s00464-001-9025-6
|View full text |Cite
|
Sign up to set email alerts
|

Does training in a virtual reality simulator improve surgical performance?

Abstract: A method that can measure surgical skill, based on the scoring of independent observers who view videotaped performances, seems to be reliable. MIST-VR did not improve the surgical skills of the subjects, but the results with MIST-VR did predict surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 10 publications
0
120
0
4
Order By: Relevance
“…Most studies also used surrogate end points such as bench station or simulator tests to establish the transferability of skills, instead of assessing skills in real operations. The conclusion of the meta-analysis was that only few studies possess the necessary quality, that two studies showed a positive effect23 24 (real operation) and one study no effect25 (simulated operation) of simulator based training. Another common feature of the previous studies is that they were all carried out using basic skills rather than procedure specific simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies also used surrogate end points such as bench station or simulator tests to establish the transferability of skills, instead of assessing skills in real operations. The conclusion of the meta-analysis was that only few studies possess the necessary quality, that two studies showed a positive effect23 24 (real operation) and one study no effect25 (simulated operation) of simulator based training. Another common feature of the previous studies is that they were all carried out using basic skills rather than procedure specific simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that simulators are valid instruments in the acquisition of MIS skills. 6,[8][9][10] Hamilton et al 11 established that laparoscopic skills developed outside the operating room are transferrable to actual performance of laparoscopic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 21 studies that surveyed whether the training intercession brought about the change of execution time, 13 (62%) investigations announced factually statistically significant improvement. For instance, in one study scientists announced that the control group took 58% longer to play out the surgery 23 and in another study specialists detailed that the control group, all things considered, played out the surgery twice the length of the intervention group (24 minutes when contrasted with 12 minutes, p < 0.001). 24 In yet another investigation the intervention group was 29% quicker in dismembering the gallbladder during a cholecystectomy than the control one.…”
Section: Performance Time (N = 13 Studies)mentioning
confidence: 99%
“…Three (14%) of the 21 examines detailed huge change on suturing, cutting, and cautering abilities 8,23,24 in the training group when contrasted with the control group.…”
mentioning
confidence: 99%